Vorticity analysis within multiple deformable inclusions under pure shear - Dasgupta, Ritabrata (International Journal of Advanced Geosciences, 2014)
This work is aiming at analyzing the vorticity vector in 2D of deformable inclusions with the help of analytical techniques. The considerations made are first, inclusions are initially spherical, deformable; second, strain distribution within the inclusions are not homogeneous . The ratio of inclusion diameter (“a”) to mean inter-inclusion distance (“b”) that is (a/b) is less than about 0.6 .Considering ‘strain rate’ as natural strain the rate is infinitesimally small . Vorticity of particles inside the inclusions is also estimated while accounting different competency contrast conditions between matrix and inclusions. It is seen that competency contrast is inversely proportional to the vorticity value. Also after a threshold value the vorticity spin becomes opposite in directional sense. Probable reasons for this hiatus are discussed. Keywords: Deformable Ductile Inclusions, Pure Shear, Vorticity, Viscosity / Competency Contrast.